International economics - Carbaugh, Robert J. (Mason, OH Cengage, 2026)
"I believe the best way to motivate students to learn a subject is to demonstrate how it is used in practice. The first eighteen editions of
International Economics reflected this belief and were written to provide a serious presentation of international economic theory, with an
emphasis on current applications. Adopters of these editions strongly supported the integration of economic theory with current events"--
Provided by publisher
Includes index.
Keywords: International economic relations